Hungarian apple growing and marketing on the doorstep of the European Union - Kállay, E.; Kállay, T. (International Journal of Horticultural Science, 2005)
The scope of apple growing and marketing has been determined by the economic and political systems in the recent decades. One may follow the booms and collapses in the Hungarian apple industry. Re-establishment of the market economy gives new chances for recovery in the fruit section as well. Reconstruction of the apple industry has started with private ownership of lands. In the present work we characterise the still existing apple farms inherited from the previous system, present the newly established orchards in detail, deal with the present state of apple commerce and finally, we try to predict the near future of Hungarian apple industry.